SOSIALISASI DIGITAL BRANDING BAGI PEMILIK USAHA KECIL DAN MENENGAH DI LINGKUNGAN LEMBAGA PEMBERDAYAAN MASYARAKAT REMPOA MELALUI MEDIA SOSIAL - Rd. Bily Parancika; Fauzi Isnaen; Fauzan Akbar Albastiah; Warsono Warsono (Journal of Community Service and Engagement, 2022)
With the increasingly sophisticated development of the times, there is no need to worry about where to do business because now everything can be done online. One technique that can be used when starting a small and medium business is digital branding. Digital branding makes it possible for business owners to be able to expand their market because this branding activity can be carried out more easily and reach more audiences. Thus, the Socialization of Digital Branding for Small and Medium Business Owners within the Rempoa Community Empowerment Institution through Social Media can help the community within the Rempoa Community Empowerment Institution in improving the community's economy and can make the community more productive. The method of implementing the activities carried out is in the form of sharing seasons, education, and providing materials based on several theories and experiences they have online through the zoom application.